Exploring the Effectiveness of the Learning Cycle Model in Enhancing Mathematics Learning for Students - Binti M, Mardatillah; Adeshina, Abimbola Nurudeen Gbolahan (jurnal matematika, 2024)
Purpose of the study: This study aims to determine the effectiveness of implementing the Learning Cycle model in mathematics learning.. Methodology: This type of research is pre-experimental research with The One Group Pretest-Posttest Design. The sampling technique in this study is by Multistage Sampling. The research instruments used are learning outcome tests, student activity observation sheets, and student response questionnaires. The data analysis used is descriptive analysis and inferential analysis.. Main Findings: 25 students or 89.29% achieved individual completeness and 3 students or 10.71% did not achieve individual completeness. This means that classical completeness was achieved with a normalized gain value of 0.70 in the high category. Based on this, the application of the Learning Cycle model is effective in learning mathematics for students. Novelty/Originality of this study: This study offers a new perspective by showing that the application of the Learning Cycle model significantly improves students' conceptual understanding and mathematical problem-solving skills compared to conventional learning approaches.